Optimization of Structure Parameters of Airfield Jointed Concrete Pavements under Temperature Gradient and Aircraft Loads - Bangshu Xu; Wanzhi Zhang; Jie Mei; Guangyao Yue; Laihua Yang (Advances in Materials Science and Engineering)
Daily changing temperature causes significant thermal stress in concrete pavement. Tensile stress obtained can exceed flexural tensile strength when the concrete slabs are subjected to large temperature gradient and traffic loads, resulting in pavement damages. In this paper, maximum tensile stresses in concrete slabs with different slab sizes, thicknesses, and length to width (L/W) ratios were investigated by using the finite element (FE) method. The important parameters in the design of concrete pavement are the flexural tensile strength and the fatigue limit. By analyzing the comparison results between the maximum tensile stress and the fatigue limit, the optimum slab size and the critical thickness were determined. The results indicate that the maximum tensile stress obtained is higher for larger slab size with thin thickness. Furthermore, to reduce cutting work and the amount of dowel bars, the optimum slab sizes of the regional airport concrete pavement are recommended as 4 m × 4 m to 6 m × 6 m. The critical thicknesses of 4 m × 4 m slab and 6 m × 6 m slab are determined as 28.2 cm and 34.7 cm, respectively, based on the most unfavorable coupling between positive and negative temperature gradients and the Boeing 737–800 aircraft load. Moreover, the maximum tensile stress increases as the L/W ratio increases. When the slab length is less than 6 m, it is better to use square slab in airport jointed concrete pavement (JCP).